Criterios para el otorgamiento de la bonificación diferencial en el Régimen Laboral de la Actividad Pública - Enciso Rivera, Wilfredo (Revista de Derecho, 2019)
The Civil Service Laws in Peru, regulates a remunerative concept called “Bonificación Diferencial” (Differential Bonus), designed for being paid to civil servants, but only when they hold a special kind of managerial positions called “cargos de responsabilidad directiva”. This article aims to bring up for discussion the criteria of interpretation and application of such rules by administrative and judicial authorities, because of the way they understand the very concept of “cargo de responsabilidad directiva”, which is the key concept to determinate if the Bonus should be paid or not. In order to do this analysis, certain technical aspects of the Peruvian Civil Service regulations will be reviewed.